Gemstone nomination in Vietnamese - Nguyen Van Thao; Nguyen Quynh Anh; Hoang Cong Binh (Lembaga Riset Mutiara Akbar, 2026)
This study investigates the nomination characteristics of gemstones in Vietnamese and explores how naming practices reflect Vietnamese cognitive and cultural perspectives. The research analyzed a corpus of 2,617 gemstone names collected from dictionaries and social communication sources. Using descriptive, semantic, statistical, and classification methods, the study categorized gemstone nominations into one-feature, two-feature, and three-feature models. The findings reveal that one-feature nomination is the most dominant pattern, particularly the model “type name + color,” indicating that visual perception plays a central role in gemstone identification. Two-feature nomination models occupy the second largest proportion and mainly emphasize color and origin, while three-feature models appear least frequently due to their structural complexity and limited practicality in daily communication. The study also demonstrates that Vietnamese gemstone naming practices are strongly influenced by cognitive simplicity, cultural symbolism, and commercial value. Furthermore, the incorporation of Sino-Vietnamese and Indo-European lexical elements reflects linguistic interaction and globalization within the gemstone trade. Overall, the findings contribute to understanding Vietnamese lexical semantics, cultural cognition, and nomination theory in linguistic studies.